Examining the overlap between tinnitus and depression questionnaires—protocol for an ICF based content analysis - Fuchten, Denise; Smit, Adriana L.; Stegeman, Inge (Frontiers in Neurology, 2024)
Introduction Tinnitus is a common phenomenon with an estimated prevalence of 14.4% in the adult population. The experienced severity of tinnitus varies significantly among this population. Psychological factors have been identified as major contributors to this perceived severity, and numerous studies have demonstrated a correlation between symptoms of depression and tinnitus severity. However, the assessment of tinnitus severity and depressive symptoms often relies on self-report questionnaires, which show content overlap. This can pose challenges in distinguishing both conditions and interpreting their relationship. To address these challenges, the proposed study aims to examine the overlap between tinnitus and depressive symptom questionnaires by analyzing their content based on the International Classification of Functioning, Disability and Health (ICF) framework. Methods and analysis Six validated, multi-item, self-report questionnaires measuring perceived tinnitus severity (THI, TQ, mTQ, THQ, TRQ, TFI) and seven validated, multi-item, self-report, depressive symptom questionnaires (BDI-II, HADS-D, SDS, PHQ-9, CES-D, SCL-90-R depression subscale, DASS-42 depression subscale) will be included in the content analysis. The content of all items of these questionnaires will be linked to ICF categories and item overlap between the tinnitus and depressive symptom questionnaires will be analyzed. Discussion By exploring the overlap between depression and tinnitus questionnaires, this study seeks to gain a better understanding of the relationship between tinnitus and depression, by distinguishing between shared content and independent constructs of symptom scores and shedding light on the factors influencing their measured severity. Ethics and dissemination Ethical approval is not required for this study, due to the characteristics of the study design. Findings will be disseminated through peer-reviewed open access publication and scientific conferences.